3D game development Cube-It : customized furniture and product design - Lai, Shi Min (2016)
BACKGROUND : I will be doing a project on product design for this joining system and device, Cube-It. Basically Cube-It is a cube which connects and locks a joint with tight fitting mechanism. It have attachable rods so it can transform into any forms, shapes and sizes. Cube-It comes in different materials and sizes. The Cube-It is able to withstand a substantial amount of weight and has strong interlocking devices to keep it firm and compact. CubeIt is known for its strength and versatility, which allows it to build anything as long as there is creativity and imagination. MOTIVATIONS : The Cube-It is versatile and can be used in various application like construction, military, marine offshore, oil and gas etc. However, we have decided to focus on designing furniture with the use of Cube-It My goal is to allow clients to personalised their furniture using Cube-It. I will be using 3D virtual modelling to show the designs. The furniture will be crafted for shared spaces in homes. At the end of this furniture design, I aim to produce something that is user friendly as well as aesthetically pleasing.